2016
DOI: 10.3390/ijms18010051
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Nodes and Cancer Metastasis: New Perspectives on the Role of Intranodal Lymphatic Sinuses

Abstract: The lymphatic system is essential for transporting interstitial fluid, soluble antigen, and immune cells from peripheral tissues to lymph nodes (LNs). Functional integrity of LNs is dependent on intact lymphatics and effective lymph drainage. Molecular mechanisms that facilitate interactions between tumor cells and lymphatic endothelial cells (LECs) during tumor progression still remain to be identified. The cellular and molecular structures of LNs are optimized to trigger a rapid and efficient immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 195 publications
(297 reference statements)
0
34
0
Order By: Relevance
“…It presents a great challenge to develop more effective therapeutic strategies to prevent metastases and recurrence. For the purpose of uncovering the CSCs and immune suppression-related genetic alterations underlying metastasis in HNSCC, we chose 15 of the CSCs and immune suppression-related genes that have been reported in the primary expression of HNSCC before (Kosan and Kunz, 2002;Grosse-Gehling et al, 2013;Nor et al, 2014;Prakasam et al, 2014;Yang et al, 2014;Hartomo et al, 2015;Wu et al, 2015;Ji, 2016;Ren et al, 2016) performed RT-PCR to examine the expression levels of in cancer tissues, lymph nodes, and the matched normal tissues from the same patients with synchronous nodal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…It presents a great challenge to develop more effective therapeutic strategies to prevent metastases and recurrence. For the purpose of uncovering the CSCs and immune suppression-related genetic alterations underlying metastasis in HNSCC, we chose 15 of the CSCs and immune suppression-related genes that have been reported in the primary expression of HNSCC before (Kosan and Kunz, 2002;Grosse-Gehling et al, 2013;Nor et al, 2014;Prakasam et al, 2014;Yang et al, 2014;Hartomo et al, 2015;Wu et al, 2015;Ji, 2016;Ren et al, 2016) performed RT-PCR to examine the expression levels of in cancer tissues, lymph nodes, and the matched normal tissues from the same patients with synchronous nodal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…MS. It was speculated that the tumor-associated lymphatics and draining LNs are key modulators of tumor cell migration and invasion by mechanisms that remain unclear (41). Furthermore, the cells migrating to the LN could have an effect on lymphatic permeability in case of inflammatory conditions (42).…”
Section: Tumor Model and Metastases Invasion Of Lnmentioning
confidence: 99%
“…Accordingly, another mechanism of tumor EMT-independent metastasis, namely tumor-induced lymphangiogenesis, has been proposed [95] . Briefly, mesenchymal cancer cells, which are able to produce and release lymphangiogenic factors, such as vascular endothelial growth factor C and D (VEGF-C and VEGF-D), promote an increase of lymphatic vessel density in the peri-and intratumoral area, so that epithelial cells are able to colonize lymphatic system and lymph nodes can facilitate their entry into the systemic circulation [96][97][98][99][100] . It has been demonstrated that an increase in lymph vessel density, due to tumor-induced lymphangiogenesis, is correlated with a high amount of lymph node metastasis, VEGF-C expression and worse disease-free/overall survival in BC patients [101] .…”
Section: Ctcs Migration Modelsmentioning
confidence: 99%